Optical Store Banten Optical Profit Loss Statement - Irsya Septiana, Fadia (Indonesian Operations Research Association (IORA), 2020)
Banten Optical Store is an outlet that carries out business activities in the eyewear sector. The Banten Optical store generates its main income from the sale of glasses, but this shop is still difficult to find out. Analysis of the profit from its sales. Therefore, a profit and loss financial statement was made to analyze the profit of the Banten Optical Store in the period January 2022 and February 2022. In making this report, the method used was collecting data from the store which included revenue and assets. This profit and loss financial statement can also help store owners to find out the income from store profits.